The effect of specific HIIT training with an intensity between the anaerobic threshold and the psychomotor fatigue threshold on the physiological parameters of young soccer players - Chmura, P.; Chmura, J.; Chodor, W.; Drozdzowski, A.; Rokita, A.; Konefal, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Effective HIIT training requires determining the individual intensity that optimally stimulates the development of exercise capacity [1]. To achieve this, it is necessary to determine the minimum intensity at the anaerobic threshold (TAN) and the maximum intensity at the psychomotor fatigue threshold (PFT) [2,3]. The aim of the study was to assess the effect of specific HIIT training, performed between the TAN and the TPF on the physiological parameters of young soccer players. In addition, the aim of the study was to determine whether in 4x4 games on a 25x35 m pitch, the tested players exceed the anaerobic threshold and are able to achieve TPF intensity.